Occupational therapists' perceptions of occupation in practice: An exploratory study. (26th April 2016) - Di Tommaso, Amelia; Isbel, Stephen; Scarvell, Jennie; Wicks, Alison
Abstract : Background/aim: The World Federation of Occupational Therapists' minimum standards state occupation and its relationship with health must be concepts covered in occupational therapy education. Therefore, it is assumed that Australian graduates have sound knowledge of the principles of occupation‐based practice. In some practice settings, the link to occupation may not be explicit and graduates could face challenges to being occupation‐based. The aims of this pilot study were to explore graduates' perceptions of occupation in their practice and to investigate whether graduates felt sufficiently prepared for occupation‐based practice. Methods: Two focus groups with eight therapists in total were employed to uncover experiences and perceptions of occupation. Themes were synthesised using Braun and Clarke's method of thematic analysis, where line by line coding was employed to inductively build themes. Results: Participants believed that occupation‐based practice was important but did not necessarily need to be implemented as a means of intervention. From the participants' perspective, simply striving for occupation as the end goal of therapy was acceptable. A strong focus on impairment‐based practice hindered some therapists from exploring the use of occupation‐based practice. For recent graduates, workplace culture was pervasive and inhibited the use of occupation. In addition, participants felt university educators did not provide an integrated or consistent approach when teaching how to apply occupation in practice. Conclusion: Workplace expectations and limited power to influence practice are impeding graduates from authentically applying occupation in practice. Insights from recently graduated therapists about occupation have the potential to inform future directions of occupation‐based practice.